Psychometric Properties of the HADS Measure of Anxiety and Depression Among Multiple Sclerosis Patients in Croatia - Jerković, Ana; Proroković, Ana; Matijaca, Meri; Vuko, Jelena; Poljičanin, Ana; Mastelić, Angela; Ćurković Katić, Ana; Košta, Vana; Kustura, Lea; Dolić, Krešimir; Ðogaš, Zoran; Rogić Vidaković, Maja (Frontiers in Psychology, 2021)
Depression and anxiety are common complaints in patients with multiple sclerosis (MS). The study objective was to investigate the factor structure, internal consistency, and correlates of the Croatian version of the Hospital Anxiety and Depression scale (HADS) in patients with MS. A total of 179 patients with MS and 999 controls were included in the online survey. All subjects completed the HADS and self-administered questionnaires capturing information of demographic, education level, disease-related variables, and the Multiple Sclerosis Impact Scale-29 (MSIS-29). Psychometric properties were examined by estimating the validity, reliability, and factor structure of the HADS scale in patients with MS. The two HADS subscales (anxiety and depression) had excellent internal consistencies (Cronbach’s α value .82 to .83), and factor analysis confirmed a two-factor structure. The convergent validity of the HADS subscales appeared to be good due to the significant correlations between HADS and MSIS-29. ROC analysis indicates that the HADS subscales have a significant diagnostic validity for group differentiation. Hierarchical regression analysis using MSIS-29 subscales as criterion variables showed consistent evidence for the incremental validity of the HADS scale. The HADS is a reliable and valid self-assessment scale in patients with MS and is suggested to be used in clinical monitoring of the psychiatric and psychological status of patients with MS.